The physical properties of lead borate (PbO-B203) glass / Mardhiah Abdullah ... [et al.] - Abdullah, Mardhiah; Wan Hussin, Wan Mohd Hanif; Kassim, Azman; Yahya, Norihan (2015)
Due to its special properties for optical material and excellent glass forming materials, borate glass with composition xPbO-(l00-x) BZ0 3 where x varying from 20 to 40 mol % are prepared by melt quenching techniques. The physical properties of glasses have been identified such as density, molar volume, X-ray diffraction (XRD), microhardness and FTIR spectroscopy measurement. The glass densities were found to be increased from 4.1848 gcm-3 to 5.2099 gcm-3. Besides, the increment in molar volume from 23.9757 cm3mor l to 25.1536 cm3morl PbO-B20 3 glasses with an increase in the PbO content has been observed and discussed. The X-ray diffraction pattern of PbO-B20 3 shows the broad humps which confirms amorphous nature in the glass networking since no peak has been observed in the diffraction pattern. The FTIR study shows that the incorporation of PbO as network modifier helps in converting B03 group to B04 units. This reveals that when PbO ions enter the glass structure it can alter the glass networking. Based on the microhardness study, it was found that the microhardness showed linear decrease from 386 kg/mm2 to 280 kg/mm2 with an increase in the PbO contents. The results will be discussed and presented in details.